CRTAM+ NK cells endowed with suppressor properties arise in leukemic bone marrow. Issue 5 (21st February 2019) - Ramírez‐Ramírez, Dalia; Padilla‐Castañeda, Sandra; Galán‐Enríquez, Carlos Samuel; Vadillo, Eduardo; Prieto‐Chávez, Jessica Lakshmi; Jiménez‐Hernández, Elva; Vilchis‐Ordóñez, Armando; Sandoval, Antonio; Balandrán, Juan Carlos; Pérez‐Tapia, Sonia Mayra; Ortiz‐Navarrete, Vianney; Pelayo, Rosana
Abstract: Due to their increasing rates of morbidity and mortality, childhood malignancies are considered a global health priority, with acute lymphoblastic leukemias (ALLs) showing the highest incidence worldwide. Control of malignant clone emergence and the subsequent normal‐leukemic hematopoietic cell out‐competition require antitumor monitoring mechanisms. Investigation of cancer surveillance innate cells may be critical to understand the mechanisms contributing in either disease progression or relapse, and to promote displacement of leukemic hematopoiesis by the normal counterpart. We report here that NK cell production is less and low hematopoietic progenitor numbers contribute to this defect. By investigating the expression of the activation molecule class I restricted T‐cell associated molecule (CRTAM) along the hematopoietic lineage differentiation pathway, we have identified lymphoid precursor populations coexpressing CD34, CD56/CD3/CD19, and CRTAM as the earliest developmental stage where activation may take place in specialized niches that display the ligand nectin‐like‐2. Of note, bone marrow (BM) from patients with ALL revealed high contents of preactivated CD56 high NK cells expressing CRTAM and endowed with an exhaustion‐like phenotype and the functional capability of producing IL‐10 and TGF‐β in vitro. Our findings suggest, for the first time, that the tumor microenvironment in ALL directly contribute to exhaustion of NK cell functions by the CRTAM/Necl‐2 interaction, and that the potential regulatory role of exhausted‐like NK cells may favor malignant progression at the expense of anti‐tumor responses. Phenotypic and functional identity of this unique suppressor‐like NK cell population within the leukemic BM would be of special interest for the pathobiology of ALL and development of targeting strategies. Abstract : Developing CRTAM + NK cells in hematopoietic niches within ALL BM respond to mesenchymal stromal cells expressing Necl‐2 by displaying an exhausted‐like immunosupressor phenotype. Exhausted CRTAM + NK cells may promote suppressor microenvironments and tumor progression.